2019
DOI: 10.1002/nml.21389
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit and public sector interorganizational collaboration in disaster recovery: Lessons from the field

Abstract: Recent disasters have identified that interorganizational collaboration is often fraught with complexity. This article explores interorganizational collaboration in the nonprofit and public sectors during the disaster recovery efforts after a catastrophic flooding event. Based on a series of in‐depth interviews with practitioners involved in the recovery following a flooding event, the findings offer insights into the barriers and mechanisms used to facilitate collaboration. In disaster recovery, collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 62 publications
3
52
0
Order By: Relevance
“…Therefore, cross-sector collaborations are increasingly referred to as an effective tool to address many social problems, especially in emerging and developing countries, where institutions are weak and lack capacity in many cases (Curnin and O'Hara, 2019, Lu and Li, 2020, Vopni, 2020. When such countries face emergencies like COVID-19, the importance of cross-sector collaboration becomes even more paramount; the public sector (state) lacks the capacity to deal with and control the spread of the virus.…”
Section: Cross-sector Collaboration In Response To Social Problemsmentioning
confidence: 99%
“…Therefore, cross-sector collaborations are increasingly referred to as an effective tool to address many social problems, especially in emerging and developing countries, where institutions are weak and lack capacity in many cases (Curnin and O'Hara, 2019, Lu and Li, 2020, Vopni, 2020. When such countries face emergencies like COVID-19, the importance of cross-sector collaboration becomes even more paramount; the public sector (state) lacks the capacity to deal with and control the spread of the virus.…”
Section: Cross-sector Collaboration In Response To Social Problemsmentioning
confidence: 99%
“…Interorganizational networks describe systems of “high interdependence among otherwise autonomous agencies” (Lawless & Moore, 1989, p. 1167). Scholars have long recognized the importance of interorganizational networks among nonprofit, business, and governmental organizations in service delivery and addressing complex social challenges in areas such as education (Selden et al, 2006) and disaster relief and recovery (Curnin & O'Hara, 2019). NPOs collaborate with others to exchange information, share resources, and conduct joint programs to address social problems that single organizations could not tackle alone.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although prior works have generated important insights to advance our understanding of how NPOs structure dyadic partnerships or collaboration networks to achieve collective goals for social impact, they lack insight into how organizations configure their egocentric networks at the meso‐organizational level. This question becomes increasingly pressing as many studies have shown the challenges and obstacles to collaboration, including management complexity, culture clash and competing institutional logics, coordination fatigue, loss of autonomy, lack of trust, and power imbalance (Curnin & O'Hara, 2019; Popp, Milward, MacKean, Casebeer, & Lindstrom, 2014), as well as individual nonprofits' struggles (e.g., lack of resources and capacity) within networks (AbouAssi, Makhlouf, & Whalen, 2016; Kim & Peng, 2018). Such challenges may keep NPOs from realizing their collaborative aspirations or prevent NPOs from collaborating at all.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A second related issue that needs to be assessed by an NGO concerns the role it wants and is able to play in the collaboration. Taking an intermediary role or advocating for insider/outsider coordination requires that an NGO is in the right position to play such role, mainly in relation to its independence from all the other parties involved in the issue and the existence of trusting relationships among actors (Curnin & O'Hara, ; Simo & Bies, ). In this respect, Oxfam's internal assessment of the situation seems to have neglected this, as it conceived its strategy solely on the idea that it could increase its position of power within SHAD using the pressure of the more pronounced and critical NGOs as a form of backing.…”
Section: Conclusion: Framing As a Screening Device For Strategic Actionmentioning
confidence: 99%